Constitutional Rights and Judicial Independence: Lessons from Iowa - Ian Bartrum (Washington University Law Review, 2011)
As was true across the country, the elections held in Iowa this past November were tough on incumbents. In Iowa, however, it was not just legislative and executive candidates that fell at the hands of an angry and confused electorate — three members of the state supreme court also lost their jobs after a controversial and closely contested judicial retention election. Iowa, like several other states, has adopted a version of the Missouri Plan of merit-based judicial selection, in which the justices of the supreme court appear periodically on the statewide ballot for a retention vote. This year, that vote was held in the shadow of the court’s controversial opinion in Varnum v. Brien, in which the justices unanimously struck down the state’s ban on same-sex marriage. In response, a coalition of socially conservative Iowans, under the loose leadership of former high school principal Bob Vander Plaats, mounted a vigorous campaign to oust those justices that happened to be up for retention. With the aid of a tremendous influx of out-of-state money, Vander Plaats’s efforts succeeded in unseating Chief Justice Marsha Ternus and Justices Michael Streit and David Baker. All three were talented jurists and dedicated public servants, and their departure is a profound loss to the state. With that said, I think it is important to consider ways to restructure and improve a judicial retention process that badly failed Iowans in 2010.
Keywords: Constitutional law -- Iowa; Judicial process; Judicial selection